2014
DOI: 10.1111/jsm.12601
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction at the Onset of Type 2 Diabetes: The Interplay of Depression, Hormonal and Cardiovascular Factors

Abstract: Introduction Several data have emphasized the importance of early diagnosis of erectile dysfunction (ED) and meticulous cardiovascular investigation in the type 2 diabetic mellitus (T2DM) patients. Aim To estimate the prevalence of ED and its associated determinants in a sample of male patients with new or recently diagnosed T2DM. Methods The SUBITO-DE study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 44 publications
1
93
1
3
Order By: Relevance
“…This finding is not surprising as it is consistent with the reduced efficacy seen for all available treatments for ED in patients with diabetes. This is likely due to the presence of multiple diabetes-associated complications, such as peripheral neuropathy and vasculopathy, including macroangiopathy, microangiopathy, and E U R O P E A N U R O L O G Y X X X ( 2 0 1 7 ) X X X -X X X endothelial dysfunction, which are not necessarily due to androgen deficiency [42][43][44][45]. In addition, TD induced by metabolic diseases is usually mild.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is not surprising as it is consistent with the reduced efficacy seen for all available treatments for ED in patients with diabetes. This is likely due to the presence of multiple diabetes-associated complications, such as peripheral neuropathy and vasculopathy, including macroangiopathy, microangiopathy, and E U R O P E A N U R O L O G Y X X X ( 2 0 1 7 ) X X X -X X X endothelial dysfunction, which are not necessarily due to androgen deficiency [42][43][44][45]. In addition, TD induced by metabolic diseases is usually mild.…”
Section: Discussionmentioning
confidence: 95%
“…Corona et al conducted a prospective study of 499 patients with newly or recently diagnosed diabetes. 35 They reported that, around the time of diagnosis of diabetes, the prevalence of premature ejaculation, delayed ejaculation and low sexual desire was 28.3%, 32.9% and 58.4%, respectively. Sexual dysfunction preceded the diagnosis of diabetes in 30%, and 45.3% had never consulted about sexual dysfunction.…”
Section: Diabetes and Other Sexual Dysfunctionsmentioning
confidence: 99%
“…Sexual dysfunction preceded the diagnosis of diabetes in 30%, and 45.3% had never consulted about sexual dysfunction. 35 T2DM has also been associated with diseases that can indirectly cause sexual dysfunction, such as balanitis and Peyronie's disease. In a study conducted in 1,137 Danish patients, a higher HbA1c level was associated with an increased frequency of balanitis in patients with diabetes compared with those without (OR 1.25, CI 1.09 to 1.44), despite adjustment for age, sex, body mass index, blood pressure, complications and antihypertensive treatment.…”
Section: Diabetes and Other Sexual Dysfunctionsmentioning
confidence: 99%
“…Importantly, a common incidence of sexual dysfunctions, usually erectile dysfunctions, has also been confirmed in men newly diagnosed with diabetes mellitus [13].…”
Section: Risk Factors Of Erectile Dysfunction Incidencementioning
confidence: 96%
“…Early diagnosis of ED in patients with diabetes mellitus can help to prevent organic and emotional disorders in these men and help to identify cardiovascular risk factors. Screening for sexual dysfunction should become part of routine diabetes care [13]. Glycaemic control optimisation, treatment of accompanying disorders and lifestyle changes are the basis for therapeutic procedure in diabetic patients [4,5,8,11].…”
Section: Introductionmentioning
confidence: 99%